Truncated differential cryptanalysis of PRINCE. Issue 16 (10th February 2015) - Zhao, Guangyao; Sun, Bing; Li, Chao; Su, Jinshu
Abstract PRINCE is a lightweight block cipher whose block size and key size are 64‐bit and 128‐bit, respectively. The core component of PRINCE is PRINCE <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgkg3jp0k8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />core</alternatives> which is wrapped by the initial and final key whitening. PRINCEcore adopts a 12‐round SPN structure. This paper exploits some new vulnerabilities of PRINCE from an aspect different from previous results, and applies truncated differential cryptanalysis to PRINCE. The result demonstrates that for several reduced versions of PRINCE, there exist 5‐round and 6‐round (out of 12 rounds) truncated differential distinguishers. We introduce a key‐recovery attack on 7‐round PRINCEcore using two 5‐round distinguishers, the data complexity is 250 chosen plaintexts and the time complexity is 248.2 7‐round encryptions, with a storage of about 222.6 counters. Both the distinguishers and key‐recovery attacks are not related to the value of α. Copyright © 2015 John Wiley & Sons, Ltd.